Functional analysis of bacterial TAL effectors and the targeted susceptibility genes in plants - Zhang, Junli (Kansas State University, 2015)
The genus Xanthomonas consists of bacterial species causing economically important plant diseases in major crops. In a wide variety of Xanthamonas species, the transcription activator-like (TAL) effectors (proteins) are synthesized and secreted into host cells, whereby they enter the plant nucleus. TAL effectors bind specific host gene promoters, inducing the expression of the targeted genes, which in some cases leads to either resistance or an enhanced state of disease susceptibility. The TAL effectors in individual Xanthomanas species and their targets in host plants have been characterized in relatively few cases. The premier example is the induction of any one member of a clade of sugar transporter genes in rice by TAL effectors of the bacterial blight pathogen X. oryzae pv. oryzae, where induction of the susceptibility (S) genes was shown to be required for the disease process. TAL effector genes are present in a wide variety of Xanthomonas species other than X. oryzae pv. oryzae. My dissertation focuses on the characterization of the TAL effectors in the citrus bacterial canker (CBC) and soybean bacterial pustule pathosystems. In CBC, CsLOB1 was identified as the S gene targeted by multiple major TAL effectors from CBC causal strains. Furthermore, another two members in family of citrus LBD family, although not identified as targets in the field, can serve as S genes in CBC. Initial analysis of bacterial pustule disease of soybean indicates that the TAL effector TAL2 of X. axonopodis pv. glycines is a virulence effector and associated with the expression of two candidate S genes, which encode a member of the ZF-HD transcription factors and a member of aluminum activated malate transporter family. These studies will enhance our understanding of plant-bacterial interactions and evolution of disease susceptibility, and also inform development of durable disease resistant crop varieties.
Keywords: Xanthomonas; Transcription activator-like effectors; Susceptibility genes; Citrus bacterial canker; Agriculture, General (0473)